The role of fertilizer in sustaining food security and protecting the environment to 2020 - Bumb, Balu L.; Baanante, Carlos A. (International Food Policy Research Institute, 1996)
In this discussion paper ... [the authors] ... review past trends in fertilizer use, estimate future needs, and assess technical and policy measures for dealing with environmental and energy concerns related to fertilizer use--P. v.